2015
DOI: 10.1038/srep13000
|View full text |Cite
|
Sign up to set email alerts
|

Rheostatic Regulation of the SERCA/Phospholamban Membrane Protein Complex Using Non-Coding RNA and Single-Stranded DNA oligonucleotides

Abstract: The membrane protein complex between sarco(endo)plasmic reticulum Ca2+-ATPase (SERCA) and phospholamban (PLN) is a prime therapeutic target for reversing cardiac contractile dysfunctions caused by calcium mishandling. So far, however, efforts to develop drugs specific for this protein complex have failed. Here, we show that non-coding RNAs and single-stranded DNAs (ssDNAs) interact with and regulate the function of the SERCA/PLN complex in a tunable manner. Both in HEK cells expressing the SERCA/PLN complex, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
(73 reference statements)
1
13
0
Order By: Relevance
“…As RNA length increases, inhibition is gradually relieved, with the 50-mer re-establishing SERCA basal activity. This is similar to the incremental relief we have previously observed for ssDNA (12). The random sequence library that was used in these experiments confirms that the RNA-PLN interaction is sequence-independent.…”
Section: Rna Sequences Bind Phospholamban With Low Nanomolar K Dsupporting
confidence: 72%
See 4 more Smart Citations
“…As RNA length increases, inhibition is gradually relieved, with the 50-mer re-establishing SERCA basal activity. This is similar to the incremental relief we have previously observed for ssDNA (12). The random sequence library that was used in these experiments confirms that the RNA-PLN interaction is sequence-independent.…”
Section: Rna Sequences Bind Phospholamban With Low Nanomolar K Dsupporting
confidence: 72%
“…In the current study, we report that many XNAs bind PLN with similar strong affinity to what was found previously for SPIDRs (12). These molecules, which are tunable by length, would allow clinicians to match the reversal of SERCA inhibition to the severity of the disease.…”
mentioning
confidence: 57%
See 3 more Smart Citations